China steps out Beijing's major power engagement with the developing world - Eisenman, Joshua 1977-; Heginbotham, Eric (Routledge Taylor & Francis Group, 2018)
"What are Beijing's objectives towards the developing world and how they have evolved and been pursued over time? Featuring contributions by recognized experts, China Steps Out analyses and explains China's strategies in Africa, the Middle East, Central Asia, Latin America, South Asia, and Southeast Asia, and evaluates their effectiveness. This book explains how other countries perceive and respond to China's growing engagement and influence. Each chapter is informed by the functionally organized academic literature and addresses a uniform set of questions about Beijing's strategy. Using a regional approach, the authors are able to make comparisons among regions based on their economic, political, military, and social characteristics, and consider the unique features of Chinese engagement in each region and the developing world as a whole. China Steps Out will be of great interest to students and scholars of Chinese foreign policy, comparative political economy, and international relations".